Complete the expression subtracting the radicals.

_ and _(radical) - _ and _ (radical) = _ and _(radical)

1 answer

To complete the expression, let’s fill in the blanks with arbitrary values. Here is an example:

5 and 2 (√3) - 3 and 4 (√3) = 2 and -2 (√3)

Breaking it down:

  1. \(5 - 3 = 2\) (whole numbers)
  2. \(2 (√3) - 4 (√3) = -2 (√3)\) (subtracting the radicals, you can treat them as like terms)

So, the complete expression is:

5 and 2 (√3) - 3 and 4 (√3) = 2 and -2 (√3)

Feel free to provide specific values if you want a more tailored expression!